The Influence of Self-Confidence on English Speaking Ability of Grade XII Students: A Study at SMKN 3 Karawang - Widiyanto, Kelvin Pramudya; Srisudarso, Mansyur; Ahmad, Yousef Bani (IKIP Siliwangi, 2025)
English is the main international language. In educational institutions, English is taught from an early age. Among other English language skills, Speaking is a crucial ability to develop in English. However, students continue to struggle with remembering all of the English vocabulary and speaking English in front of the class. Self-confidence is one of the factors that influence English language proficiency. Therefore, this study was done to assess the influence of self-confidence on the English speaking skill in grade XII students at SMKN 3 Karawang. This study uses quantitative research with a non-probability sampling method with a snowball sampling technique. The instrument in this study uses a self-confidence questionnaire based on Schwarzer's theory and an English-speaking ability questionnaire based on Brown's theory which was constructed by the researcher himself. Respondents in this study amounted to 240 respondents who were calculated based on the Slovin formula with a 5% error rate. The results of this study show a sig. Value. 0.000<0.005 means that self-confidence influences the ability to speak English in class XII students at SMKN 3 Karawang with a large influence of self-confidence of 15%.